Genre-based and Process-based on Writing Skill - Musdalifah, Musdalifah (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2025)
The ability to write a text is important for students to develop. However, not everyone can carry out and make this skill an easy and popular activity. Various groups of students who study at university are important to make this writing activity a pleasure, as it will aim to convey ideas more broadly. Not only that, but they will also compile their final project or thesis as students. In this case, it is important to be carried out, especially in sharpening thinking patterns, conveying ideas, and providing new experiences in learning English, especially in writing activities. This research covers an implementation of learning writing through a genre-based and process-based approach. It uses a research method with a type of comparison that distinguishes between two independent variables. The result of this study, based on the significance of a t-test score, is 0.887, which is higher than 0.05, meaning that there is no significant difference between learning by using a process-based approach and a genre-based approach on writing skill. The researcher used a sample by dividing the class into two groups using a post-test score.